Trade in the Ports of Bushire, Khorramshahr, Bandar Abbas, Bahrain, Kuwait and Muscat in 1936 A Study Based on Frank Todd’s Report - Al Omari, Thabet Ghazi; bani Issa, Abdalmoiz (Jordan Journal for History and Archaeology, 2023)
This article deals with the commercial conditions in the Arab Gulf region in 1936 based on the report prepared by Frank Todd, the British Vice Consul in Bushire. This paper studied only six Gulf ports included in the report, three of which were on the eastern bank of the Arabian Gulf, namely Bushire, Khorramshahr, Bandar Abbas, and three Arab ports, namely Bahrain, Kuwait, and Muscat. The study provides a clear and integrated picture of their commercial conditions, especially in terms of trade movement, participating countries, exchanged commodities, and financial statements related to exports and imports in terms of increase or decrease. The most prominent finding of this paper was the continuation of British trade in those ports, but not at the level desired by the British government, as its trade witnessed a decline in some ports due to international competition, especially from Japan.